2004
DOI: 10.1603/0022-2585-41.3.321
|View full text |Cite
|
Sign up to set email alerts
|

Triatoma ryckmani(Hemiptera: Reduviidae) in the EpiphyteTillandsia xerographica(Bromeliaceae) in the Semiarid Region of Guatemala : Table 1

Abstract: For the first time, the reduviid bug Triatoma ryckmani Zeledón and Ponce (Hemiptera; Reduviidae) was recorded to inhabit the epiphyte Tillandsia xerographica Rohweder (Bromeliaceae) in the semiarid region of Guatemala. These bromeliads grow mainly in drought-resistant trees with rough bark such as Pereskia lychnidiflora (Cactaceae). In our study site, we investigated 30 T. xerographica, and 53 specimens of T. ryckmani were found. Most T. ryckmani (68.5%) were unfed. Ants (Formicidae) were the predominant (92.2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 2 publications
0
5
0
Order By: Relevance
“…Given that (1) triatomines can live for several months in starvation, (2) the vast majority of insects sampled here were adults, which ingest proportionally smaller blood meals than nymphs, and (3) many field studies have found that specimens are often starved at the moment of collection, it was not surprising that we were able to confirm putative sources of blood meal from just 25% of the abdomens analyzed [ 80 83 ]. Nevertheless, the fact that contamination from human handling was uniformly present across samples, the RADseq approach was arguably least effective at resolving vector-feeding patterns, and is likely to be useful only for very recent or large blood meals.…”
Section: Discussionmentioning
confidence: 99%
“…Given that (1) triatomines can live for several months in starvation, (2) the vast majority of insects sampled here were adults, which ingest proportionally smaller blood meals than nymphs, and (3) many field studies have found that specimens are often starved at the moment of collection, it was not surprising that we were able to confirm putative sources of blood meal from just 25% of the abdomens analyzed [ 80 83 ]. Nevertheless, the fact that contamination from human handling was uniformly present across samples, the RADseq approach was arguably least effective at resolving vector-feeding patterns, and is likely to be useful only for very recent or large blood meals.…”
Section: Discussionmentioning
confidence: 99%
“…More recently, the natural habitats of T. ryckmani were discovered in a semiarid region of El Progreso Department, Guatemala, in cacti (Stenocercus eichlamii) and epiphytic bromeliads (Tillandsia xerographica). In the first instance, all instars of the bug were found in the dry portions of the cactus (Marroquín et al 2004a, Monroy et al 2004; in the second situation, colonies of the bugs were also found within the leaves of the bromeliads growing on trees, including the cacti (Marroquín et al 2004b). The species has also been found in at least four Departments of Nicaragua in small numbers in houses, under intra and peridomiciliary conditions (Marín et al 2006 Here we describe, for the first time, the entire life cycle of T. ryckmani under laboratory conditions and the blood patterns of the different instars from specimens collected under natural conditions in Guatemala.…”
mentioning
confidence: 99%
“…ryckmani, which occurs in Guatemala and Honduras (Zeledón and Ponce, 1972;Carcavallo et al, 1999;Marroquín et al, 2004;present study), sometimes in domestic areas (present study), should not be overlooked. The involvement of Tri.…”
Section: Discussionmentioning
confidence: 50%